Chakravyuha sculpted in stone - Mahabharata - 55 - Brig Ajai Singh (2022)
Image courtesy: Brig A.P. Singh - www.collectingmoment.in A rare sculptural depiction of the complex Chakravyuha fighting formation from the Mahabharata.